2022
DOI: 10.1371/journal.pone.0273503
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni and soil-transmitted helminths among schoolchildren in An-Nadirah District, Ibb Governorate, Yemen after a decade of preventive chemotherapy

Abstract: The Ministry of Public Health in Yemen continues the implementation of school and community–based preventive chemotherapy with praziquantel and albendazole for the control and elimination of schistosomiasis and soil-transmitted helminths (STH). The latest remapping to update the distribution of schistosomiasis and STH was conducted seven years ago. This study aimed to estimate the prevalence, intensity and associated risk factors of Schistosoma mansoni and STH among schoolchildren in An-Nadirah District, Ibb G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…These eggs can be ingested by humans if they do not wash their hands before consuming food. This is consistent with research conducted by Hohmann, et al (2001) Tefera, et al (2017 and Al-Murisi, et al (2022) which found a significant association between Ascaris lumbricoides infection in children and the habit of washing hands after defecation and before meals.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These eggs can be ingested by humans if they do not wash their hands before consuming food. This is consistent with research conducted by Hohmann, et al (2001) Tefera, et al (2017 and Al-Murisi, et al (2022) which found a significant association between Ascaris lumbricoides infection in children and the habit of washing hands after defecation and before meals.…”
Section: Resultssupporting
confidence: 93%
“…Severe infections can cause intestinal obstruction (EC & DL., 2022;Nurmantu et al, 2023). Several studies have shown a relationship between hygiene behavior and STH infections in children (Al-Murisi et al, 2022;E. Tefera et al, 2017).However, there is still a lack of systematic review specifically addressing the association between hygiene behavior and Ascaris lumbricoides infections among children in the Southeast Asian region.…”
Section: Introductionmentioning
confidence: 99%